Admiration Over Time. (26th November 2020) - Archer, Alfred; Matheson, Benjamin
Abstract: In this paper, we investigate the diachronic fittingness conditions of admiration – that is, what it takes for a person to continue or cease to be admirable over time. We present a series of cases that elicit judgements that suggest different understandings of admiration over time. In some cases, admirability seems to last forever. In other cases, it seems that it can cease within a person's lifetime if she changes sufficiently. Taken together, these cases highlight what we call the puzzle of admiration over time . We then present a potential solution to this puzzle.